PENGARUH PEMBERIAN INFORMASI KESEHATAN MENGGUNAKAN MEDIA WHATSAPP DALAM MENINGKATKAN DUKUNGAN SUAMI TERHADAP ANTENATAL CARE PADA IBU HAMIL DI KECAMATAN PADANGSIDEMPUAN UTARA - Erlindai Erlindai; Valentina Valentina; Esraida Simanjuntak (Jurnal Maternitas Kebidanan, 2021)
Maternal mortality can be prevented through the Antenatal Care program. Antenatal Care coverage for K4 in North Padangsidimpuan District was 76.75%. K4 coverage has not yet reached the national target of 85%. One factor that causes pregnant women to be incomplete in making visits is low husband support. Spouse support can be improved by providing fast and precise health education media via Whatsapp. This study used a quasi-experimental design with pre-test-post-test group design. The study population was a combination of 47 pregnant wives. The sample was partly couples with 41 pregnant wives, which were taken by purposive sampling. Data analysis used the Wilcoxon test with 95% Confidence Interval (CI). The statistical results obtained that the average value of partner support regarding antenatal care in pregnant women after being given health information using Whatsapp media was higher than the average value of husband's support before being given intervention, which was from 10.83 to 14.05. There is an effect of presenting health information using Whatsapp media in increasing husbands support for antenatal services to pregnant women in North Padangsidempuan District (p = 0.000). It is recommended PuskesmasPadangsidempuan Utara to provide health information about antenatal care to increase husband support for pregnant women.